Contemporary Studies in Entrepreneurship: All Inclusive - Tatyana Alimova (Journal of Economic Sociology, 2014)
Today entrepreneurship as an interdisciplinary area of research attracts increased attention of representatives of different schools, being actively developed in theoretical and applied areas. But there is one unpleasant exception. Mainstream research is presented here mostly by foreign researchers whose achievements have gone far ahead of foundations laid down by Max Weber and Joseph Schumpeter, but they are little known for wide audience of Russian lecturers and students, which are together storming economic, sociological, psychological and managerial principles of entrepreneurship.The reviewed book has all the reasons to fill this information gap in, as it introduces a reader to the formed approaches and ongoing discussions on theory, methodology and practice of entrepreneurship research at the international level. After all, there is a collection of articles on the creative biography and scientific contributions of the winners of the most prestigious in its field International Prize for Research of Small Business and Entrepreneurship, which was founded jointly by Swedish Foundation for Small Business Research (FSF) and Swedish Agency for Economic and Regional Growth (NUTEK) in 1996. Adding the whole picture, specially prepared lectures of the Prize winners accent the priority and the most promising directions for further research in this area. In addition an extensive bibliography, finalizing excursus into laureates’ achievements and forming “knowledge platforms” on the main aspects of research at the international level is there.